Association between cardiac pathology and outcomes of patients with COVID-19 using a hand-held ultrasound. (14th October 2021) - Dadon, Z; Levi, N; Orlev, A; Belman, D; Alpert, E A; Steinmetz, Y; Wolak, A; Glikson, M; Gottlieb, S; Butnaru, A
Abstract: Background: The association between COVID-19 infection and the cardiovascular system has been well described. Strict precautions limit the use of formal echocardiography in this setting. Information on the importance of the utilization of a hand-held point-of-care cardiac ultrasound (POCCUS) for cardiac evaluation in these patients is scarce. Objective: To investigate the utilization of hand-held echocardiography in COVID-19 hospitalized patients and the association between cardiac pathologies and outcomes. Methods: Consecutive patients diagnosed with COVID-19 underwent POCCUS evaluation using a hand-held ultrasound within 24 hours of admission at our institute, throughout March-May 2020. According to the POCCUS results, the patients were divided into two groups: 'Normal' and 'Abnormal' (including left or right ventricular dysfunction or enlargement, or moderate/severe valvular regurgitation/stenosis). Results: Among 102 patients, 26 (25.5%) had an abnormal POCCUS study. They were older, with more co-morbidities, cardiovascular disease history, chronic medical therapy, and more severe presenting symptoms, as compared to the group with a normal echocardiography exam. Individual and composite endpoints (advanced ventilatory support, acute decompensated heart failure, shock, or death) are presented in Table 1. Multivariate logistic regression analysis adjusting for pertinent variables revealed that abnormal echocardiography at presentation was independently associated with the composite endpoint OR=4.63 (95% CI 1.51–14.15, p=0.007). Conclusions: Abnormal echocardiography results in COVID-19 infection settings are associated with a higher burden of medical comorbidities and independently predict major adverse endpoints. Hand-held POCCUS at presentation can be utilized as an important tool for risk stratification for hospitalized COVID-19 patients. Funding Acknowledgement: Type of funding sources: Private hospital(s). Main funding source(s): SZMC Scientific